Long-term results of endoscopic treatment of vesicoureteral reflux with the sub-ureteric injection of calcium hydroxyapatite - ŞİMŞEK, FERRUH; TİNAY, İLKER; TARCAN, TUFAN (SPRINGER, 2007)
Aim To review our long-term results of the sub-ureteric injection of calcium hydroxyapatite in the endoscopic management of vesicoureteral reflux (VUR) in children. Materials and methods A sub-ureteric injection of calcium hydroxyapatite was given to 14 children (23 ureteral units) affected by VUR grades I-V. All children were followed-up with monthly urine cultures, and a renal ultrasound was done on the postoperative 4th week, while the first voiding cysto-urethrogram (VCUG) control was performed on postoperative week 12. The children were followed-up with yearly renal ultrasound and monthly urine cultures, thereafter. Data from the patients' charts were retrospectively analyzed regarding the outcome of the procedures. Results Mean follow-up time was 52 months (47-60 months). VUR was cured in 47.4% of cases after a single injection. After the second injection the global success rate was 52.1%. Ureteroneocystostomy was performed on seven refluxing ureters of five children unresponsive to sub-ureteric injection therapy. One patient underwent nephroureterectomy because of a non-functioning kidney secondary to ureteral obstruction due to migration of material at the 23rd month postoperatively. Conclusion Although favorable short-term success rates have been reported with the sub-ureteric injection of calcium hydroxyapatite without any side effects, our long-term results showed a low success rate, with the only reported serious morbidity.
Keywords: calcium hydroxyapatite; sub-ureteric injection; vesicoureteral reflux; MIGRATION; SILICONE; TEFLON